Factors influencing clinical decision-making and health-related quality of life changes in colorectal cancer patients receiving targeted therapy: a multicenter study in China - Zeyang Li; Chengxi Feng; Hongwei Liu; Yin Liu; Huifang Xu; Yuqian Zhao; Xi Zhang; Yanqin Yu; Shaokai Zhang; Youlin Qiao (BMC Cancer)
Abstract Objectives The aim of this paper is to assess the current clinical application of targeted therapy in colorectal cancer (CRC), identify factors influencing patients’ acceptance of targeted therapy, and evaluate its impact of targeted therapy on patients’ health-related quality of life (HRQoL). Methods This study was based on a national multi-center survey. From March 2020 to March 2021, involved 19 tertiary hospitals across seven regions in China through multi-stage stratified sampling. CRC patients who underwent genetic testing participated. Data on demographic and clinical characteristics, disease knowledge, medical service utilization, medical expenditure, and HRQoL before and after treatment were collected through face-to-face interviews. Logistic regression identified factors affecting therapy acceptance, while the HRQoL changes in pre-and post-treatment were compared by the Mann-Whitney U test. Results Among 1,468 eligible patients, 79.7% were aged 50+, 60% male, and 31.5% retired. Secondary education was the most common level (30.3%). A total of 62.7% of patients received targeted therapy. Multivariable analysis showed that metastasis at diagnosis, out-of-pocket expenses, and reimbursement ratio were positively associated with targeted therapy (P < 0.05), while initial diagnosis stage, region, and genetic testing reimbursement were negatively associated (P < 0.05). Post-therapy, patients’ quality of life declined significantly (P < 0.001), especially in fatigue and financial burden. Conclusions Our study revealed multiple factors influencing CRC patients’ acceptance of targeted therapy and found that targeted therapy may adversely affect HRQoL. These findings emphasize the necessity of implementing more comprehensive patient management strategies to optimize the clinical application of targeted therapy and improve patients’ quality of life.